2020
DOI: 10.1002/cplu.202000477
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Mediated versus Tetrazine‐Triggered Bioorthogonal Release Reactions: Direct Comparison and Combinations Thereof

Abstract: Bioorthogonal cleavage reactions are gaining popularity in chemically inducible prodrug activation and in the control of biomolecular functions. Despite similar applications, these reactions were developed and optimized on different substrates and under different experimental conditions. Reported herein is a side‐by‐side comparison of palladium‐, ruthenium‐ and tetrazine‐triggered release reactions, which aims at comparing the reaction kinetics, efficiency and overall advantages and limitations of the methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Toward this goal, we employed our recently developed TCO-caged resorufin dye conjugate (TCO-Reso). 53 Our initial experiments performed in a well plate format revealed that tetrazines bearing a single methyl substituent release almost 50% of the resorufin dye from TCO-Reso within the first hour. In contrast, tetrazines having an aryl substituent at this position displayed a rather slow gradual release of the dye over 12 h (Figure S21B).…”
Section: Mitochondria-specific Release Reaction In Live Cellssupporting
confidence: 74%
See 1 more Smart Citation
“…Toward this goal, we employed our recently developed TCO-caged resorufin dye conjugate (TCO-Reso). 53 Our initial experiments performed in a well plate format revealed that tetrazines bearing a single methyl substituent release almost 50% of the resorufin dye from TCO-Reso within the first hour. In contrast, tetrazines having an aryl substituent at this position displayed a rather slow gradual release of the dye over 12 h (Figure S21B).…”
Section: Mitochondria-specific Release Reaction In Live Cellssupporting
confidence: 74%
“…Because our cationic tetrazines comprise a structurally unprecedented motif, we first evaluated their releasing efficacy. Toward this goal, we employed our recently developed TCO-caged resorufin dye conjugate (TCO-Reso) . Our initial experiments performed in a well plate format revealed that tetrazines bearing a single methyl substituent release almost 50% of the resorufin dye from TCO-Reso within the first hour.…”
Section: Resultsmentioning
confidence: 99%
“…9,11,13,14 Despite proving the potential of catalysis-based approaches in medicine, the great majority of the schemes proposed so far display rather modest catalytic efficiencies, even in buffer solutions, as evidenced by low turnover numbers (TONs) and slow reaction kinetics. 15 The latter aspect is especially overlooked by the scientic community working in this eld, yet of key importance in the development of drug activation strategies. Apart from few exceptions, 2,12,16,17 catalysts currently reported in the literature typically achieve substrate conversion rates in solution that are in the order of 0.1-10 h À1 (10 À3 to 10 À1 min À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…prodrug) to induce the desired therapeutic effects. In such a scenario, the catalyst intrinsic toxicity is critical 15 and the choice of drugs with high-potency (sub-μM) becomes often mandatory, overall limiting the therapeutic scope of several catalysis-based strategies for prodrug activation.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, pretreatment of cells with Pd reagents followed by the addition of the pro-fluorophore failed to generate any fluorescent signal, presumably because of the conversion of Pd complexes to inactive species. In another study, it was observed that even in simple systems such as phosphate-buffered saline, transition metal catalysts underwent partial deactivation [ 118 ].
Fig.
…”
Section: Reactions In Mitochondriamentioning
confidence: 99%